A Systems study on Century Pipes Corporation - Ayes, Sheryl; Buyco, Joyce Dawn.; Dompor, Maria Lorena; Ocampo, Elaine (Diliman, Quezon City College of Engineering, 2003)
Century Pipes Corporation (CPC) is a company engaged in manufacturing industrial pipes. It was established on January 2000 and since then has offered low cost and quality pipes to different households in Luzon through their supply chain. The company is presently operating 24 hours a day, 7 days a week, with only the last Sunday of the month allotted for cleaning, checking and maintenance of machines. However, even if the company is operating almost nonstop, it cannot still meet its customers demand. Using a SWOT (Strengths, Weaknesses, Opportunities and Threats) Analysis, the strength defined is also the competitive priority recognized by the company. With as much as 35% of the regulated marketing price for PVC pipes, CPC is one of the cheapest producers of PVC pipes. However, the company?s current low production level does not support this goal. Other strength defined is good feel over their daily operations. For the company?s weaknesses, the following are identified: not being able to meet customer demand, not financially strong at the moment, limited control over their suppliers, and limited knowledge about their production capacity. Opportunities and threats to look out for are: increasing demand of uPVC pipes, and existence of potential market in Visayas and Mindanao for the opportunities; and the risk of being shut down because of occupational health risks posed by the company?s operations to its workers, emerging competition, economic crisis, and the long term threat of government passing a law to regulate the use of PVCs because of its harmful effect to those exposed to it for prolonged periods of time for the threats. With the help of TOWS Analysis, different solutions were identified to make use of the company?s strengths to capitalize on benefits presented by the opportunities. It should also aid in lessening the immediate and long-term effects of the threats identified. The weaknesses defined, on the other hand, should be improved through either change in the current systems or through working within the boundaries of the opportunities, whichever is applicable. The strengths, weaknesses, threats and opportunities identified together with the solutions were further evaluated using different tools in problem-solving. Through the aid of Stream Diagnostic Chart, the problems of not meeting customer demand, greater health risks posed by the company?s operations and poor planning were identified. Ishikawa Diagrams aid in determining the root causes of these problems. These root cause are then verified using Root-Cause Verification Matrix. Afterwards, several alternatives for the main root causes were generated. Each alternatives were evaluated to come up with the most feasible and helpful recommendations to the company. Cost-Benefit Assessment and Analysis also aided in evaluating the alternatives generated. The alternatives chosen are: *Subcontract PVC scrap collection, *Perform preventive and corrective maintenance on a regular basis, *Buy critical machine parts, *Provide poka yokes on the work area, *Impose strict supervision of crusher operators/sorters, *Assess performance of crusher operators/sorters, *Monitor the screw and barrel alignment regularly, *Observe strict implementation of SOP, *Record orders in a logbook, *Present the study results to upper management. All these proposed alternatives resulted to positive B/C ratios which imply that the solutions presented are indeed attractive and are highly recommendable for implementation. The greatest emphasis should be given on the suggestions which are aimed to improve the efficiency of management because the bulk of the problem being addressed is on the aspect of planning. An implementation plan was also devised and Gantt charts were provided for each of the plans. Gantt charts show that all the chosen alternatives could be implemented in a span of six (6) months starting from April this year. Others should be done continually from the time it is implemented.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 155 : Industrial Systems Design
Keywords: Century Pipes Corporation (CPC); Plastics industry and trade--Management.; Polyvinyl chloride; System design